Application of good milking practices: economic impacts and bovine raw milk quality - Melo Soares, Évelyn Silva de; Duarte, Marjorie Toledo; Carrijo, Kênia Fátima; Costa, Marcela Rezende (Multitemas, 2019)
The aim of this study was to evaluate the effects of application of the good milking practices on economic aspects as well as on microbiological and sanitary characteristics of raw milk and bovine mammary gland of animals from Sidrolandia/MS farms. A questionnaire was applied to verify the utilization of good milking practices and milk samples of each property were collected from the expansion tanks to evaluate total bacteria and somatic cell counts as well as milk composition and frauds presence, before and after training the farms employees in good milking practices. The farms that adopted the measures of milking hygiene reduced the bacteria and somatic cell counts, what caused increase on milk quality, better mastitis control and greater bonus payment by the industry to the producers. Thus, incorporation of good milking practices promoted positive impacts on socio-economic aspects and milk quality.